Hypoplastic Left Heart Syndrome: Is There a Role for Fetal Therapy? - Tulzer, Andreas; Huhta, James C.; Hochpoechler, Julian; Holzer, Kathrin; Karas, Thomas; Kielmayer, David; Tulzer, Gerald (Frontiers in Pediatrics, 2022)
During fetal life some cardiac defects may lead to diminished left heart growth and to the evolution of a form of hypoplastic left heart syndrome (HLHS). In fetuses with an established HLHS, severe restriction or premature closure of the atrial septum leads to left atrial hypertension and remodeling of the pulmonary vasculature, severely worsening an already poor prognosis. Fetal therapy, including invasive fetal cardiac interventions and non-invasive maternal hyperoxygenation, have been introduced to prevent a possible progression of left heart hypoplasia, improve postnatal outcome, or secure fetal survival. The aim of this review is to cover patient selection and possible hemodynamic effects of fetal cardiac procedures and maternal hyperoxygenation in fetuses with an evolving or established hypoplastic left heart syndrome.